Role of Charge Traps in the Performance of Atomically Thin Transistors. Issue 19 (15th March 2017) - Amit, Iddo; Octon, Tobias J.; Townsend, Nicola J.; Reale, Francesco; Wright, C. David; Mattevi, Cecilia; Craciun, Monica F.; Russo, Saverio
Abstract : Transient currents in atomically thin MoTe2 field‐effect transistors (FETs) are measured during cycles of pulses through the gate electrode. The curves of the transient currents are analyzed in light of a newly proposed model for charge‐trapping dynamics that renders a time‐dependent change in the threshold voltage as the dominant effect on the channel hysteretic behavior over emission currents from the charge traps. The proposed model is expected to be instrumental in understanding the fundamental physics that governs the performance of atomically thin FETs and is applicable to the entire class of atomically thin‐based devices. Hence, the model is vital to the intelligent design of fast and highly efficient optoelectronic devices. Abstract : Transient currents in atomically thin MoTe2 field‐effect transistors (FETs) are measured during cycles of gate pulses. The curves of the transient currents are analyzed using a newly proposed model for charge‐trapping dynamics that renders a time‐dependent change in the threshold voltage as the dominant effect on the channel behavior. The model is instrumental in understanding the fundamental physics that governs the performance of atomically thin FETs.